The economic paradigms need to be updated - Jaroslav Daňhel; Eva Ducháčková; Jarmila Radová (European Financial and Accounting Journal, 2016)
This contribution deals with the current problems of the stagnating European economy: a high level of debt, political instability and a lower level of ethics. The growth of the income gap in society is viewed as one of the most pressing problems. Reference is made to the ineffectiveness of traditional fiscal and monetary policy, the problematic nature of solutions based on new tools, such as quantitative easing, and the low level of the effectiveness of implemented regulatory projects, which reduce the efficiency of regulated business. In a quest for new approaches to correcting economic paradigms, the authors recommend greater anticipation of empirical and behavioural approaches, or, possibly, even a return to the beginning - ie. to the ideas of the free market.
Keywords: A11; B41; D69; D74; G02; G22; 650; Behavioural approaches; Economic paradigms; State regulation